NtCIPK9: A Calcineurin B-Like Protein-Interacting Protein Kinase From the Halophyte Nitraria tangutorum, Enhances Arabidopsis Salt Tolerance - Lu, Lu; Chen, Xinying; Zhu, Liming; Li, Mengjuan; Zhang, Jingbo; Yang, Xiuyan; Wang, Pengkai; Lu, Ye; Cheng, Tielong; Shi, Jisen; Yi, Yin; Chen, Jinhui (Frontiers in Plant Science, 2020)
Calcinerin B-like protein-interacting protein kinases (CIPKs) play essential roles in plant abiotic stress response. In order to better understand salt tolerance, we cloned and analyzed the NtCIPK9 gene from the halophyte Nitraria tangutorum, which plant is close to citrus in Sapindales clade by evolutionary study. Phylogenetic analysis shows that NtCIPK9 belongs to a sister clade with the Arabidopsis AtCIPK9 gene and is thought to localize to the plasma membrane. NtCIPK9 shows the highest expression level in the Nitraria tangutorum root under normal growth conditions, whereas after NaCl treatment, the highest expression was found in the blade. NtCIPK9-overexpressing Arabidopsis plants have a higher seed germination rate, longer root length and displayed higher salt tolerance than wild type seedlings under salt stress conditions. Furthermore, NtCIPK9 overexpression enhances AtHKT1 expression and improves K+ content in transgenic seedlings after NaCl treatment. Thus, we conclude that NtCIPK9 increases transgenic plant salt tolerance and reduces damage associated with salt stress by promoting the expression of genes controlling ion homeostasis. Our results suggest that NtCIPK9 could serve as an ideal candidate gene to genetically engineer salt-tolerant plants.